Traditional Saami reindeer herding village resource territories on the western Kola Peninsula, Russia - Wheelersburg, Robert P.; Gutsol, Natalia (Polar Record, 2009)
ABSTRACT Some Arctic scholars believe that modern reindeer herding on the Kola Peninsula has cultural continuity with the traditional period of such activity in the late 19th century. Others believe that by World War II, Soviet repression of Saami leaders, collectivisation of herding villages, and relocation of families had eliminated many traditional behaviours, especially in the Lake Imandra watershed. This study utilises informant interviews with survivors of the Babinski and Ekostrovski Saami reindeer herding villages and archival materials to understand how their families used land and water to fish, hunt, and obtain other resources including cash labour. As part of the United States National Science Foundation's human dimensions of the Arctic system (HARC) programme to examine how humans are both shaped by, and shape, the Arctic environment, the authors document how lands and waters formed traditional resource territories for Saami herding families. The results reveal that prior to their destruction, western Kola reindeer herding villages were integrated along family lines, with villages sharing mates, resource territories, and economic activities. This paper argues that there was, in fact, no cultural continuity between traditional Saami reindeer herding villages and modern herding structures such as the post-Soviet brigade on the western Kola Peninsula.